Desain Pesan Pembelajaran di Era Digital - Nanang Gesang Wahyudi (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2019)
This paper aims to examine the problems of learning paradigm changes caused by technological developments in education in the digital era and provide solutions for teachers to improve the quality of learning. This study uses qualitative research methods with a literature review approach. Research by exploring the latest and most trusted reference sources is then explored in full and in depth. The results of this study note that technological developments in education led to a shift in the pattern of learning approaches that used to teacher-centered to be student-centered. Learning problems that arise as a result of technological developments in the digital era include; students in the digital age can access science through online with a laptop or smartphone, so that the source of knowledge obtained is less accountable, students are less interested in the design of learning messages taught without innovative media, teachers as facilitators are still lacking in using information technology-based media and communication in improving the quality of learning. This is a challenge for the teacher as a communicator in learning communication. The solution to these problems is that the teacher must active role in validating the source of information obtained by the student's knowledge, so that its validity can be accounted. Teachers need to design learning messages effectively so that students as communicants can receive learning messages well. Teachers need to have the right strategy in utilizing information and communication technology-based learning media in order to improve the quality of learning.